Padrão clínico-epidemiológico das pneumonias por Human bocavirus em crianças de até cinco anos atendidas em um hospital de referência na cidade de Fortaleza-Ceará - Campelo, Felipe Serra (2021)
Pneumonia is an important public health problem in developing countries, representing one of the main causes of hospitalization and death in children. Human Bocavirus (HBoV) is a causative agent of upper and lower respiratory infections, mainly affecting children under five years of age. The aim of this study is to describe the prevalence of HBoV and the clinical and epidemiological characteristics of children affected by this agent in the city of Fortaleza, Ceará. For this purpose, nasopharyngeal aspirates were collected from 545 children up to five years old treated at a reference pediatric hospital in Fortaleza. Children diagnosed with pneumonia between January 2013 and December 2014 were included. The samples were submitted to PCR for detection of HBoV and parainfluenza 4 (PIV4) and indirect immunofluorescence for detection of respiratory syncytial virus (RSV), adenovirus (AdV), influenza A and B (FLU A and FLU B) and parainfluenza virus 1, 2 and 3 (PIV1, PIV2, PIV3). Most of the children were seen in the emergency/observation rooms (279/545; 51.1%), and in the wards (208/545; 38.1%). Of the total samples analyzed, 359 (65.8%) were positive for at least one virus investigated. Of these, 70.8% (254/359) of the samples had a single virus detected and 29.2% (105/359) had two viruses or more. HBoV was detected in 87 samples (15.9%), being the second most prevalent virus, behind RSV (150 / 27.5%). PIV3, AdV, PIV4, PIV1, FLU A, FLU B, and PIV2 were behind HBoV with 86 (15.7%), 45 (8.2%), 42 (7.7%), 33 (6%), 30 (5.5%), 3 (0.5%) and 3 (0.5%) detections, respectively. Of the 87 samples positive for HBoV, 44 (50.5%) were coinfections with other viral agents, with 15 (34%) coinfections occurring with RSV, 12 (27.2%) with PIV3 and five (11.30%) with PIV4 as the most frequent agents detected concomitantly with HBoV. The mean age of children infected with HBoV was 12.1 months and the most frequent symptoms were cough, dyspnea, and fever. In addition, 90.6% of HBoV-positive children received antibiotics for the empirical treatment of pneumonia. HBoV did not present any pattern of circulation, but it was more frequent in the first half of the year, totaling 68.9% of cases. HBoV is a frequent agent of pneumonia in the study population